Living Qur’an dalam Media Sosial: Resepsi Al-Qur’an dalam Film Animasi Upin & Ipin Iqra’ Episode Surah Al-Falaq - Fikri, Ahmad (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the reception of the Qur'an in the animated film Upin & Ipin IQRA' episode “Surah Al-Falaq” as a form of Living Qur'an practice in digital media. Using a qualitative approach through literature review and content analysis, this study employs Ahmad Rafiq's theory of Qur'anic reception, which divides reception into exegetical, aesthetic, and functional aspects. The results show that this episode, produced by Les' Copaque Production, displays aesthetic reception through the visualization of the mushaf, recitation, and verse subtitles; exegetical reception through explanations of the meaning and stories of the Prophet related to the context of the surah; and functional reception through the practice of Surah Al-Falaq as a prayer for protection. Substantively, the message presented is in line with the interpretations in Tafsir Al-Qur'an Al-'Adzhim, Fi Zhilalil Qur'an, and Tafsir Al-Misbah, so that this film represents the transformation of theological messages from interpretive texts to a communicative visual medium without losing the substance of tawhid and its spiritual protection values.